MACULAR OCULAR COHERENCE TOMOGRAPHY CHANGES IN PATHOLOGICAL MYOPIA. - Samina Karim1 , Nazullah2, Musawer Javed3 , Najmul Hassan 4 , Muhammad Asif5 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: Myopia is one of the most common refractive error which affecting 27% of world population OBJECTIVES: To study the role of ocular coherence tomography (OCT) in detecting the macular changes in pathological myopia. STUDY DESIGN: Observational case study. PLACE AND DURATION OF STUDY: This study was carried out at the Department of Clinical Ophthalmology, Khyber Girl’s Medical College, Hayatabad Medical Complex (HMC), Peshawar over a period of six months from 10th September 2021 to 10th March 2022. PATIENTS AND METHODS: This was an observational case study. There were 70 eyes of 35 patients and both male and female were included in the study. First the visual acuity, refraction and detail slit lamp examination of all the patients was carried out in the OPD. The axial length was measured with A-Scan. Then ocular coherence tomography (OCT) was done in all the patients and the findings were documented in given proforma. RESULTS: this study include 70 eyes of 35 patients. In whom 22 male and 13 female patients. The range of the age was 11 to 60 years. All the included patients have pathological myopia. Whose refractive error was more than -6.00 diopter and axial length was more than 26 mm. The macular changes seen in 60% of the cases. .In which the most common changes in high myopic patients was the combination of different macular pathologies. This was present in 22 eyes (31.1%). The other pathologies include ERM, retinoschisis, foveoschisis, PVD, Macular hole and CNV was also seen in our study. CONCLUSIONS: It was concluded that ocular coherence tomography play an important role in detecting the different macular changes in high pathological myopic patients. Which was some time not visible on ophthalmoscopic examination?